Development of Teachers’ Beliefs as a Core Component of their Professional Identity in Initial Teacher Education: A Longitudinal Perspective - Vlasta Vizek Vidović; Vlatka Domović (Center for Educational Policy Studies Journal, 2019)
The main aim of this research is to longitudinally examine the shift in teaching students’ professional beliefs about the teacher-pupil role during the course of their studies. The starting assumption has been that teachers’ professional development is largely dependent upon their beliefs about various aspects of their professional role. The beliefs about the teacher-pupil role are the building blocks of teachers’ professional identity, which strongly influence the way they teach and communicate with pupils. The participants in the research are 62 student teachers, from three teacher education faculties, who were prepared to teach in the lower grades of primary school. The research was carried out in two waves, at the beginning and at the end of the five-year study programme. The beliefs were explored using a metaphor technique derived from the cognitive theory of metaphor. The results indicate that exposure to the study programme did not considerably affect the change in the belief orientations, meaning that pre-professional beliefs remained unchanged, especially in the perception of the pupil’s role. That finding has been discussed in relation to the possible implications for the initial teacher education curriculum and its implementation.